2021
DOI: 10.5433/1679-0359.2021v42n2p907
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of chemical composition, in vitro gas production, metabolizable energy, net energy lactation values of different peanut varieties and line by Hohenheim in vitro gas production technique

Abstract: This study was carried out to determine the nutritional value of some selected peanut varieties and line in the Eastern Mediterranean Agricultural Research Institute of Adana, Turkey. The peanut varieties used were Gazipasa, Sultan, NC7, Cihangir, and Halisbey; while the peanut line was DA335/2011. The chemical composition, metabolizable energy (ME), net energy lactation (NEL) and organic matter digestibility (OMD) of the selected peanut varieties and line were determined through Hohenheim in vitro gas product… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
2
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 27 publications
2
2
1
Order By: Relevance
“…The difference between all stages in terms of CP ratios was significant (p<0.001). The results of chemical analysis of Phacelia showed that CP content decreased with the growth and maturity of the plant, which is consistent with the results of some previous studies (Soya et al, 1999;Kamalak et al, 2014;Kaplan et al, 2017;Ayaşan et al, 2021). In another study (Geren et al, 2007) on two different Phacelia cultivars, it was observed that the mean values of the ratio CP were lower than the values obtained for all four stages in this study.…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…The difference between all stages in terms of CP ratios was significant (p<0.001). The results of chemical analysis of Phacelia showed that CP content decreased with the growth and maturity of the plant, which is consistent with the results of some previous studies (Soya et al, 1999;Kamalak et al, 2014;Kaplan et al, 2017;Ayaşan et al, 2021). In another study (Geren et al, 2007) on two different Phacelia cultivars, it was observed that the mean values of the ratio CP were lower than the values obtained for all four stages in this study.…”
Section: Resultssupporting
confidence: 92%
“…al. 2020aAyaşan et al, 2021). Lower ADF ratios than in our study were observed in alfalfa, vetch, pea, bird's-foot trefoil and colza dried grasses, but the NDF ratios observed in alfalfa, vetch and pea in the same study were similar to those in our study (Canbolat and Kara, 2013).…”
Section: Resultssupporting
confidence: 84%
See 1 more Smart Citation
“…In forage plants, quality is associated with the contents of nutrients and toxic substances. It is affected many factors such as ecological conditions, plant species and variety, harvest time, and fertilizer (Gülcan et al 2002;Ayasan et al, 2021). Feed quality, that is, the capacity to provide the desired nutrients to ruminant animals, (Adesogan et al, 2006;Newman et al, 2006;Muir et al, 2007) is economically important in selling or purchasing (Schut et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…In ruminant determination of nutritional value of feeds and the effect of various processes including heat treatment is important, also it is important to study the amount of disappearance in the rumen, intestine and the entire gastrointestinal tract, which can be examined using methods such as nylon bags, gas production technique and three-step laboratory method (Ayasan et al, 2021).…”
Section: Ruminal and Post Ruminal Degradabilitymentioning
confidence: 99%